Fusobacteria behaving badly: Masquerading strains of strictly anaerobic Escherichiacoli misidentified due to the deletion of the hemB gene. (February 2023) - Endres, Bradley T.; Basseres, Eugenie; Citron, Diane M.; Tyrrell, Kerin L.; Begum, Khurshida; Lancaster, Chris; Warren, Yumi A.; Alam, M. Jahangir; Garey, Kevin W.; Goldstein, Ellie J.C.
Abstract: Three strictly anaerobic strains of Escherichia coli were misidentified as Fusobacterium mortiferum, due to a deletion of the hemB gene which is involved in anaerobic respiration. An unusual antimicrobial susceptibility pattern sparked the further diagnostic strategies that eventually identified these strains as true anaerobic E. coli This phenomenon is more common than appreciated and can have an impact on clinical practice including persistent and relapsing infections. Highlights: Colonial morphology and susceptibility patterns disparities are rarely investigated Metronidazole resistant Fusobacterium species are rare Deletion of the hemB gene in E coli may cause misidentification as fusobacterium This misidentification can lead to improper abx therapy and recurrent infection. This phenomenon is widespread and underappreciated.